2019
DOI: 10.1016/j.heliyon.2019.e02486
|View full text |Cite
|
Sign up to set email alerts
|

Se and I status in pregnant ewes from a pastoral system and the effect of supplementation with Se and I or only Se on wool quality of lambs

Abstract: Australian Merino ewes and lambs producing fine fibre wool for export are raised in the north-west of Uruguay in pasture-based systems. We studied the status of selenium and iodine in pregnant Merino ewes (10 per treatment) grazing in natural pasture, in natural pasture and supplemented with Se (0.1 mg Se/kg dry matter intake) and I (1 mg I/kg dry matter intake), or in natural pasture and supplemented with Se alone (0.1 mg Se/kg dry matter intake), during the last 30 days of gestation. Further, we evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Iodine levels are similar to those obtained by Guerra et al [16] in Uruguay. According to Suttle [42] the iodine requirements in animals of 50 kg average are in a range of 50-100 μg / kg DM so in the present study the requirements of this mineral were covered during the experiment.…”
Section: Content Of Se I Ndf and Cp In Natural Pasturessupporting
confidence: 90%
“…Iodine levels are similar to those obtained by Guerra et al [16] in Uruguay. According to Suttle [42] the iodine requirements in animals of 50 kg average are in a range of 50-100 μg / kg DM so in the present study the requirements of this mineral were covered during the experiment.…”
Section: Content Of Se I Ndf and Cp In Natural Pasturessupporting
confidence: 90%
“…Also, season and fertilization can affect the level of copper in native grass and cultivated pastures [22,26]. Suboptimal content in selenium in pasture mixed received in this study was observed previously Guerra et al [6] related to season, particularly in the littoral Region where this study was carried out. Still, it could change with the season, as reported before [6].…”
Section: Resultssupporting
confidence: 64%
“…Traditionally, sheep production in the Country carry out in pastoral systems, associated with an image of animal welfare and natural product, whose exploitation is essential for export promotion and to offer healthy food for consumers [5]. A Region in the littoral Northwest of the Country, with abundant high-quality grasses in natural conditions, is traditionally lamb producer, mainly small-scale and predominately Merino for the wool [6]. Red meat is highly nutritional and has a high biological value of protein, bioavailable iron, trace minerals, and vitamins, including a high content of B12 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Chinese Merino sheep breeds were mainly produced by crossing Tibetan or Mongolian sheep with Soviet Merino, Rambouillet sheep and Australian Merino [ 3 ]. The main distinction of fine and coarse wool sheep breeds is that the coarse wool sheep have a large amount of medullated wool, while the key to fine wool sheep breeding is to select with less medullated wool until only non-medullated wool retained [ 4 , 5 ]. The medullated wool is developed from primary wool follicle, while the non-medullated wool is developed from primary and secondary wool follicle [ 6 ].…”
Section: Introductionmentioning
confidence: 99%